Effect of volumetric modification with nanosized zirconium dioxide particles on structure and mechanical properties of composite material based on polytetrafluoroethylene - A. V. Gulkin; A. A. Teploukhov; N. A. Semenyuk; A. P. Sazankov; A. E. Kartashova; D. V. Skakun (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article demonstrates the influence of the concentration of nanosized particles of zirconium dioxide ZrO2 applied as a bulk modifier-filler on the structure and strength characteristics of polytetrafluoroethylene-based composite. samples with concentrations of 0 %, 4 %, 8 % and 26 % of ZrO2 nanosized zirconium dioxide particles were obtained by the sintering method in a mould in conditions of volumetric limitation of thermal expansion. The authors analyzed the structural-chemical state and elemental composition of the samples by X-ray photoelectron spectroscopy using Surface Science Center (Riber) and scanning electron microscopy with application of energy-dispersive analysis. Moreover, the hardness was determined on a Shore type A TWR-AM (durometer) with an analogue indicator. Wear tests were carried out on the UMT-2168 universal friction machine by the mode without lubricating fluid at the 5 N constant load, peripheral speed with the 0,32 m/s abrasive sheet. The results of the conducted research were confirmed under full-scale test conditions. As a result, the authors present recommendations on the percentage composition of nanosize filler in polytetrafluoroethylene for seals in friction units.